Carrier PWM control of cascade multilevel inverter for three-phase four-wire shunt active filter - Nguyen, Van Nho; Pham , Ngoc Hiep (Journal of Technical Education Science, 2010)
Cascade multilevel inverters are known as perspective converters for applications. They can help to use simple integrated power modulus, simplify and avoid the problem of DC source balancing. The paper introduces a new carrier PWM technique to control the cascade inverter output. Improving electrical power quality by reducing harmonic content caused by nonlinear load will be considered. In this paper, there will be mathematically formulated and simulated for 5-level cascade inverter and applied in filtering harmonics in three-phase four-wire unbalanced load system.